High-temperature performance of damaged reinforced concrete columns under post-earthquake fires. Issue 2 (1st February 2021) - Wen, Bo; Zhang, Lu; Wu, Bo; Niu, Ditao
Abstract: Post-earthquake fires (PEF) are a frequent phenomenon of earthquakes and usually causes severe damage to reinforced-concrete (RC) columns. To determine the high-temperature performance of RC columns damaged by PEF, the geometric-damage forms of concrete columns after an earthquake are mainly classified as cracking, concrete spalling, and residual deformation on the basis of existing hazard and experimental data. Full-scale seismic-damage column tests were performed to analyse the failure mode of components at a high temperature. Subsequently, the relative depth of cracks, thickness of concrete spalling, relative height of spalling, and residual deformation were proposed as geometric-damage parameters to calculate the thermal-field distribution. Finally, according to the relation between the geometric-damage parameters and the bearing capacity, equations for predicting the high-temperature bearing capacity of PEF concrete columns were established.